2004
DOI: 10.1016/j.compchemeng.2004.07.014
|View full text |Cite
|
Sign up to set email alerts
|

An online application of dynamic PLS to a dearomatization process

Abstract: Early detection of process disturbances and prediction of malfunctions in process equipment improve the safety of the process, minimize the time and resources needed for maintenance, and increase the uniform quality of the products. The objective of online-monitoring is to trace the state of the process and the condition of process equipment in real-time, and to detect faults as early as possible.In this article the different properties of the online-monitoring methods applied in the process industries are fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…Nevertheless, PLS based soft sensors are still very common in practical use [22][23][24][25], due to its simplicity and clear mathematical background. In this paper, PLS method is the basis for adaptive model building.…”
Section: Methods For Model Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, PLS based soft sensors are still very common in practical use [22][23][24][25], due to its simplicity and clear mathematical background. In this paper, PLS method is the basis for adaptive model building.…”
Section: Methods For Model Adaptationmentioning
confidence: 99%
“…Recursive NIPALS algorithm was implemented according to (22). DTM variable estimation and absolute error of the estimation are not showed since they are very similar to Fig.…”
Section: Recursive Nipals Algorithmmentioning
confidence: 99%
“…LS models had an input variable set of six variables, listed in Table 1. Partial least squares (PLS) was chosen as an FDI method due to the excellent results reported by Komulainen [13]). The PLS model for IBP was trained with six variables.…”
Section: Fdi Modelsmentioning
confidence: 99%
“…A large number of successful industrial applications of these data-based monitoring methods and ANNs have been reported (e.g. Komulainen et al [13] and Jamsa-Jounela et al [10] and Kampjarvi et al [12]) and reviewed, e.g. by Isermann and Ball [8] and Meireles et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…A fault in the analysed signal is detected when λ ≥ − n n m U (6) where λ is the threshold for fault detection. The minimum size of the detected fault (ν/2) and the detection threshold (λ) are tuning parameters, whose values were determined based on knowledge about the analysers' characteristics.…”
Section: A Dearomatisation Process Modelsmentioning
confidence: 99%